Identifying Factors Influencing the Labor Productivity of SMEs in South Sumatra - Dirta Pratama Atiyatna; Abdul Bashir; Ichsan Hamidi (Jurnal Ekonomi Pembangunan, 2021)
This study is to investigate the effect of human capital, labor domicile, gender, and working hours on the productivity of MSME workers in South Sumatra. The data used are primary data, data collection with a purposive sample approach as many as 196 samples as workers in SMEs. This study applies a logistic regression approach. The findings of this study indicate that independent tests, human capital, labor domicile, gender, and working hours have a significant relationship to labor productivity. Likewise, jointly the predictor variables such as junior high school, Local  workers, male, and working hours of more than seven hours have the opportunity to get higher productivity than other categories in SMEs.